Pemberdayaan Kewirausahaan Pelaku Usaha Lokal Dalam Mendukung Ekowisata Bromo Tengger Semeru - Halim, Rahmawati (JPS: Journal of Publicness Studies, 2026)
The Bromo Tengger Semeru National Park (TNBTS) area is a prime tourist destination with significant natural and cultural potential for the Tenggerese people. This study aims to analyze the effectiveness of empowering local businesses in supporting ecotourism, identify barriers, and analyze the gap between ideal conditions (das sollen) and reality (das sein). This study used a qualitative descriptive method, with data collection techniques through direct observation and literature review. The results indicate that although the Community-Based Tourism (CBT) concept has begun to be implemented, entrepreneurial empowerment remains suboptimal. Local businesses (homestays, culinary, transportation, and crafts) still face obstacles in access to capital, technology, and managerial skills. A gap was identified, with the community's role still predominantly at the operational level, rather than the strategic one. Sustainable synergy between the government, academics, and the community is needed to create inclusive economic independence.